Cost and Benefit Analysis of Sports Tourism in Downhill Trek, Cikole Lembang, Bandung Barat District, West Java Province - Cahyadi, Hery Sigit; Suherlan, Herlan; Dewantara , Muhammad Aldo (Politeknik Pariwisata NHI Bandung, 2021)
The purpose of the research is to analyze the cost and benefit analysis and find out the feasibility of sport tourism development at Cikole, Lembang in support the lacal community income. This research was conducted at the Downhill Track Cikole Bike Park in Lembang District and is a tourist attraction in the form of downhill bicycle track facilities. The number obtained is the result of calculating the comparison between benefits and costs and shows the value that can be defined as a feasible activity, because the numbers obtained have a value of more than 1 which is an indication of eligibility with a results in the form of> 1 declared feasible and if <1 (less of) is declared ineligible. Based on the calculation results of the Cost-Benefit Ratio (CBR) analysis with the final result in the form of a comparison value of 3,3128528. With the increase in the number of visits and opening of new jobs, the results of the analysis in the form of downhill activities have been declared feasible.